Penentuan Kadar Karbohidrat pada Biji Cempedak Hutan (Artocarpus champeden Lour.) dengan Metoda Tembaga-Iodometri - Fadjria, Neri; Zulfisa, Zulfisa; Arfiandi, Arfiandi; Yolandari, Indah (Jurnal Riset Kimia, 2019)
Forest Cempedak Seeds (Artocarpus champeden Lour.) Are types of seeds that are underutilized by humans. Forest Cempedak Seed Flour has nutritional content of carbohydrates, fats, and proteins that can be processed as ingredients for food. This study aims to determine the carbohydrate content of Forest Cempedak Seeds (Artocarpus champeden Lour.) Conducted by the Copper-Iodometric method using a luff schoorl reagent. From the research that has been carried out obtained levels of carbohydrates in Cempedak Seeds (Artocarpus champeden Lour.) of 38.016%.Â